ANALISIS DAN PERANCANGAN SISTEM PENUNJANG KEPUTUSAN PEMILIHAN GURU BERPRESTASI DENGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGTING (SAW) PADA SMK N 1 MUARO JAMBI - Yunarni Fauziah; Sarjono Sarjono (Jurnal Manajemen Sistem Informasi, 2016)
The research aims to develop decision support system. Thus it ease the process of selecting outstandingteachers and provide an alternative selection of grade system to selecting outstanding teachers. This decisionsupport system use the calculation method of Simple Additive weighting (SAW). This system can demonstratethe results of grade system for outstanding teachers, based on the calculation method of SAW. However, in theSAW method has not been able to resolve a case in which there yag same preference value. Thus, in this systemadded an algorithm to resolve the case by comparing the values in each criteria. The criteria used in this studyis the educational qualifications, tenure, value SKP, self-development and decision support prestasi.Sistemselecting outstanding teachers with SAW method can help facilitate the election of outstanding teachers andprovides an alternative method results perangkingan SAW. Future studies are recommended to develop adecision support system for the selection of outstanding teachers by using a different method or combination ofmethods SAW with other methods.